2018
DOI: 10.1089/lap.2017.0674
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prophylactic Endoscopic Sphincterotomy for Prevention of Postoperative Bile Leak in Hydatid Liver Disease: A Randomized Controlled Study

Abstract: Prophylactic ES provides significant reduction in postoperative bile leak rate with shorter hospital stay after partial cystectomy of hydatid cyst. Biliary fistula in patients with ES has significantly lower daily output with shorter time of drain removal and shorter time to closure than patients without ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, the possibility of bile leakage can be reduced by reducing the bile duct pressure through stone removal or tube insertion through ERCP before surgery. [10] When the liver injury was suspected during surgery in patients with bile duct dilatation as in the present cases, bile leakage can be prevented by suture ligation during surgery. A previous study reported that the bilirubin concentration in the drain was low during the early postoperative period when fibrin glue was applied to the cut surface after hepatectomy.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, the possibility of bile leakage can be reduced by reducing the bile duct pressure through stone removal or tube insertion through ERCP before surgery. [10] When the liver injury was suspected during surgery in patients with bile duct dilatation as in the present cases, bile leakage can be prevented by suture ligation during surgery. A previous study reported that the bilirubin concentration in the drain was low during the early postoperative period when fibrin glue was applied to the cut surface after hepatectomy.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, when the intrahepatic bile duct was dilated, and intraabdominal adhesion was suspected due to the previous history of surgery, such as cholecystectomy, we should pay more attention to avoid liver injury during adhesiolysis and perform meticulous dissections. In addition, the possibility of bile leakage can be reduced by reducing the bile duct pressure through stone removal or tube insertion through ERCP before surgery [10] …”
Section: Discussionmentioning
confidence: 99%
“…A carefully chosen site for cystectomy can decrease the chances of post-operative complications like biliary fistulae. 5 Often the cyst is first aspirated using a wide bore cannula at the proposed site of cystectomy incision, presence of clear fluid without any bile staining indicates unlikely biliary-cyst communication and the site of needle insertion can be used for cystectomy incision safely. Sites of biliary-cyst communication can be localized using the ultrasound and the surgical plan can be adapted accordingly using a more radical surgical resection, as a conservative approach is more frequently associated with postoperative cavity related complications.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled study conducted in Egypt, preoperative endoscopic sphincterotomy significantly reduced the inci-dence rate of bile leak (11.1% vs. 40.7%) and duration of fistula closure. 21 In another prospective study conducted by Sharma et al on patients with a hydatid cyst communicating with the bile duct, sphincterotomy with insertion of a nasobiliary drain (n = 6) or sphincterotomy with biliary stenting (n = 22) led to fistula healing in all patients after a median period of 11 (range, 5-45) days. 22 The removal of nasobiliary drainage catheters and stents was performed 8-45 days after stent placement.…”
Section: Staymentioning
confidence: 94%